1997
DOI: 10.1159/000289153
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits and Metabolic Control: A Study in Insulin-Dependent Diabetes mellitus Patients

Abstract: Background: In the present study the authors evaluated the relationship between personality traits (according to DSM-III-R) and poor metabolic control in an adult onset insulin-dependent diabetes mellitus sample (n = 77). Methods: Personality traits were assessed with the Personality Diagnostic Questionnaire – Revised. Metabolic control was evaluated through glycosilated hemoglobin (HbAlc): poor metabolic control was defined as HbAlc ≧ 9% (normal values < 6.0%). Results: Principal Component Analysis revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
1
1
0
1
Order By: Relevance
“…One explanation is that these symptoms are the consequences of the stress created by the effort to achieve metabolic control. Our finding that psychopathology was unrelated to poor metabolic control concurs with some research in the literature [1, 2, 4], but is in disagreement with other authors [6, 7, 8, 9]. …”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…One explanation is that these symptoms are the consequences of the stress created by the effort to achieve metabolic control. Our finding that psychopathology was unrelated to poor metabolic control concurs with some research in the literature [1, 2, 4], but is in disagreement with other authors [6, 7, 8, 9]. …”
Section: Discussionsupporting
confidence: 52%
“…In a recent study, Goldston et al [5]observed a 38.5% prevalence of psychiatric disorder in adolescents with diabetes, as compared to 20% reported in youths in a community sample; 13.2% of the former showed a predominance of suicidal thoughts. Studies [6, 7, 8, 9]have shown a significant association between psychopathology and diabetic control in children and adults, thus creating a conflicting picture. Overall, heightened anxiety, depressed mood, feelings of inadequacy, disturbed dependence-independence relations, social withdrawal, rebellion and hostility have been found in studies of children with diabetes, but not consistently [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…7 Häufigkeit klinisch relevanter ¹Fälleª (entsprechend den jeweiligen Cut-off Scores) (* = auf 5 %-Niveau signifikant; ** = auf 1%-Niveau signifikant). Studien zur Komorbidität von Eûstörungen und Typ-2-Diabetes finden sich in der Literatur vergleichsweise selten (Wing et al 1989(Wing et al , 1990Kenardy et al 1994 (Sachs et al 1992, Wrigley u. Mayou 1991, Niemeryk et al 1990, Lustman et al 1986, 1991, 1995Giles et al 1992, Orlandini et al 1997. Der psycho-somatische Zusammenhang dürfte auûerordentlich komplex sein, flieûen doch eine Vielzahl von somatischen (z.…”
Section: Diskussionunclassified